The Onset of Diabetes During Transcranial Direct Current Stimulation Treatment of Anorexia Nervosa — A Case Report - Mares, Tadeas; Ceresnakova, Silvie; Albrecht, Jakub; Buday, Jozef; Klasova, Johana; Horackova, Klara; Raboch, Jiri; Papezova, Hana; Anders, Martin (Frontiers in Psychiatry, 2020)
The relationship between tDCS (transcranial direct current stimulation) and its influence on glycemia has been the aim of limited research efforts. Usually, the focus has been set on lowering the blood sugar level or interference with insulin resistance, but also the treatment of diabetic polyneuropathy and pain management. In this case report, we outline the development of hyperglycemia and the following onset of type I diabetes during a series of tDCS in a 24-year old Caucasian female patient treated with our research protocol (10 sessions; 2mA; 30 minutes; the anode over F3; the cathode over Fp2) for anorexia nervosa.